FACTORS AFFECTING THE VALUE OF COMPANIES IN THE FOOD AND BEVERAGE COMPANIES LISTED ON BEI - Setyowati, Rini; Masitoh, Endang; Siddi, Purnama (Journal of Business, Management, and Accounting, 2020)
The increasing number of companies in the era of industrialization today, requires companies to be able to compete in national and international markets. One good company can be seen from the value of the company, maximizing company value means increasing company performance in order to achieve the company's vision. The purpose of this research is to find out whether the influence between capital structure (DER), profitability (ROA), liquidity (CR), company growth and company size on firm value. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The sample in this study were 11 companies that met the criteria in the study. Data analysis technique used is multiple linear regression. The results showed a significant influence is capital structure and profitability. The benefit of this research is to provide additional information to researchers who will develop knowledge in the field of financial accounting.